2012
DOI: 10.1152/ajpcell.00258.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibits the expression of AT1 receptors in neurons

Abstract: We have previously observed an increased of angiotensin II (ANG II) type 1 receptor (AT 1R) with enhanced AT 1R-mediated sympathetic outflow and concomitant downregulation of neuronal nitric oxide (NO) synthase (nNOS) with reduced NO-mediated inhibition from the paraventricular nucleus (PVN) in rats with heart failure. To test the hypothesis that NO exerts an inhibitory effect on AT 1R expression in the PVN, we used primary cultured hypothalamic cells of neonatal rats and neuronal cell line NG108-15 as in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 56 publications
(61 reference statements)
3
24
0
1
Order By: Relevance
“…NG108 cells have neuronal properties, are immunoreactive to renin, and have angiotensin, angiotensinogen, angiotensin-converting enzyme as well as AT 1 and AT 2 receptor subtypes (8,20,39). These cells also have endogenous expression of nNOS (23,37,38) and NMDAR (3,18,25) and therefore serve as a suitable model for studying the interplay between receptors and gene expression at the cellular level in neurons (33,36).…”
Section: Discussionmentioning
confidence: 99%
“…NG108 cells have neuronal properties, are immunoreactive to renin, and have angiotensin, angiotensinogen, angiotensin-converting enzyme as well as AT 1 and AT 2 receptor subtypes (8,20,39). These cells also have endogenous expression of nNOS (23,37,38) and NMDAR (3,18,25) and therefore serve as a suitable model for studying the interplay between receptors and gene expression at the cellular level in neurons (33,36).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal nitric oxide synthase (nNOS), which synthesizes the gaseous neurotransmitter nitric oxide, represses AT1 receptor expression in hypothalamic cell culture via a PKG-mediated mechanism [60]. A significant decrease in neurons expressing nNOS RNA and histological staining for nNOS was observed in the ventral parvocellular PVN of rats after 35 days CIH [61].…”
Section: Maintaining Hypertension—pvnmentioning
confidence: 99%
“…Within the PVN, the inhibitory neurotransmitter NO can act as part of negative feedback system for the excitatory glutamatergic system (24). Regarding the downstream influence alterations in NO may have, a recent study (36) has found that within neuronal cell lines, NO serves as a negative regulator of angiotensin type 1 receptor expression. Reductions in NO may be mediating their effects on blood pressure via glutamatergic and angiotenergic-mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%